Interplanar space-controllable carboxylate pillared metal organic framework ultrathin nanosheet for superhigh capacity rechargeable alkaline battery. (August 2019) - Li, Junpeng; Zhao, Hongyang; Wang, Jianwei; Li, Na; Wu, Miaomiao; Zhang, Qian; Du, Yaping
Abstract: Hydroxides and their derivatives as cathode materials of rechargeable alkaline batteries have limited specific capacity. In this work, a new ultrathin metal organic framework (MOF) nanosheet with expanded interplanar space is delicately designed. The organic ligand as a pillar enlarges the interplanar space for ion transportation to Ni/Co redox centers. The obtained NiCo-MOF cathode has high capacity and rate retention, specifically, 225 mAh g −1 and 82% capacity retention from 1 to 20 A g −1, which is over four-fold to that of NiCo-LDH. A full cell composed of NiCo-MOF cathode and an organic anode shows high capacity of 280 mAh g −1 with long-term cycle stability. Furthermore, we find electrochemical performance increases linearly with larger interplanar space. The present results can give new insight into structure design for advanced cathode materials and understanding the relationship between structures and performance of alkaline batteries. Graphical abstract: Carboxylate pillared ultrathin NiCo-MOF nanosheet with large interplanar space is designed to obtain high performance cathode material for rechargeable alkaline battery. The present results show capacity and rate performance increase linearly with larger interplanar space, giving us new insight into structure design for advanced cathode materials of alkaline batteries.Image 1 Highlights: The performance of NiCo-MOF cathode depends on its interplanar spaces. Enlarging interplanar spaces can facilitate electrolyte ion diffusion, which contributes to electrochemical performance. Excellent full cell performance is demonstrated in NiCo-MOF/PAQS aqueous alkaline battery.